A Noble Approach of Process Automation in Galvanized Nut, Bolt Manufacturing Industry - Akash Samanta; Arindam Dutta (Institute of Advanced Engineering and Science, 2012)
Corrosion costs money”, The Columbus battle institute estimates that corrosion costs Americans more than 220 billion annually, about 4.3% of the gross natural product [1].Now a days due to increase of pollution, the rate of corrosion is also increasing day-by-day mainly in India, so, to save the steel structures, galvanizing is the best and the simplest solution. Due to this reason galvanizing industries are increasing day-by-day since mid of 1700s.Galvanizing is a controlled metallurgical combination of zinc and steel that can provide a corrosion resistance in a wide variety of environment. In fact, the galvanized metal corrosion resistance factor can be some 70 to 80 times greater that the base metal material. Keeping in mind the importance of this industry, a noble approach of process automation in galvanized nut-bolt manufacturing plant is presented here as nuts and bolts are the prime ingredient of any structure. In this paper the main objectives of any industry like survival, profit maximization, profit satisfying and sales growth are fulfilled. Furthermore the environmental aspects i.e. pollution control and energy saving are also considered in this paper. The whole automation process is done using programmable logic controller (PLC) which has number of unique advantages like being faster, reliable, requires less maintenance and reprogrammable. The whole system has been designed and tested using GE, FANUC PLC.DOI: http://dx.doi.org/10.11591/ijra.v1i2.346